Kontakty literackie Kazimiery Iłłakowiczówny z międzywojennym Poznaniem - Biesiada, Jacek (Ecclesia. Studia z Dziejów Wielkopolski, 2012)
In the interwar period Kazimiera Iłłakowiczówna had two meetings with her audience at the invitation of the Club of Polish Literature Students and Scholars of the Poznań University - on 25 February 1930 and 9 May 1933. On 23 February 1939 she took part in the 126th Literary Thursday. She read her works, alongside Emil Zegadłowicz, on 11 April 1931 at a special literary-artistic evening organized to mark the 10th anniversary of the Trade Union of Polish Writers in Poznań. In the discussed period Iłłakowiczówna's poems and critical studies pertaining to her artistic output appeared among others in „Dziennik Poznański", „Kurier Poznański" and „Tęcza". In the years 1919-1939 Iłłakowiczówna also paid private visits to Poznań and places in its vicinity, e.g. to Wierzenica, Kwilicz, Jurkowo.